Social Responsibility - Sameera Mian (International Institute of Islamic Thought, 2000)
The 2nd Annual AMSS-UK Conference, “Social Responsibility: Challenges for the Future,” took place October 21-22 at the University of Westminster, London. Scholars from the United Kingdom, Ireland, Malaysia, the United States, Western Europe, and Turkey presented fortytwo papers. Over one hundred participants attended the two-day event. The Conference featured scholars such Malik Badri, Kamal Hassan, Murad Hofmann, Abdelwahab El-Affendi, in addition to emerging intellectuals such as Mashood A. Baderin and Fauzi Ahmad. The vital participation of graduate students and junior faculty at the AMSS-UK and the AMSS-US conference in Washington, DC, the prior weekend indicates the growing presence of Muslims in western academia. Asad Ahmad was master of ceremonies and Yusuf El-Khoie from the Khoie Foundation gave the opening remarks. The keynote address inaugurated the conference and was followed by a plenary session. Paper sessions comprised the rest of the event with a “book Iaunch” and final plenary session concluding the program Sunday afternoon. Paper sessions were organized around various subthemes directly related to social responsibility and the future. Presenters reflected upon social welfare, the state, social policy and community development, law, health and social care, grassroots action, globalization and the media, education, and methodologies and gender. The direct link between the Conference theme and paper sessions encouraged a lucid and fertile ground for intense discussion, paving the way for an emerging discourse on social responsibility in Islam. The keynote address was delivered by Kamal Hassan, rector, International Islamic University, Malaysia, and established the importance of scholars and academics in promoting social responsibility. He reflected upon the role of universities in promoting social responsibility under globalization. At present, universities are reacting to globalization by adopting a “corporatization of curriculum” and a “market driving” approach to ...